Strategi SDM untuk Meningkatkan Kinerja UMKM di Sulawesi Barat melalui Kompetensi dan Digitalisasi - Muhammad Ybnu Taufan (Jurnal Ilmiah Multidisiplin Amsir, 2026)
This study analyzes competency development and business digitalization as strategies for improving the performance of MSMEs in West Sulawesi Province from a Human Resource Management (HRM) perspective. Using a descriptive qualitative approach, data were obtained through in-depth interviews, observations, and documentation of purposively selected MSMEs, then analyzed using thematic techniques. The results indicate that competency development through training, self-learning, and improved managerial and marketing skills contribute to increased business capacity. Digitalization through social media, marketplaces, digital payments, and business applications drives operational efficiency and market expansion. These two strategies reinforce each other in increasing the productivity and competitiveness of MSMEs. Supporting factors include motivation, technological support, and access to training, while constraints include low digital literacy, limited resources, and unequal access to technology. This study confirms that competency development and digitalization are effective HRM strategies for improving MSME performance and are relevant as a basis for formulating sustainable development policies.